TANGGUNG JAWAB NEGARA INDONESIA DALAM MELINDUNGI HAK PEKERJA MIGRAN INDONESIA (STUDI KASUS: PARTI LIYANI MELAWAN CHAIRMAN DARI CHANGI AIRPORT GROUP) - Isabella Sharon Massie; Gatot S Soemartono (Jurnal Hukum Adigama, 2021)
Alluding to Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers (IMW), one of IMW's rights is to obtain legal assistance, each IMW is also obliged to follow the procedure and meet the requirements stipulated. Referring to the Decision of the Singapore Public Prosecutor v Parti Liyani District Court [2019] SGDC 57, a housemaid named Parti Liyani was slandered and reported to the police by the family of her former employer, who was an influential person in Singapore. This action was deliberately done to prevent her from filing a report to the Ministry of Manpower (MOM) Singapore, related to what was done by the family. Sentenced to 26 months' imprisonment for an act that Parti did not commit, Parti applied for a remedy. Singapore High Court Judgment [2020] SGHC 187 Magistrate's Appeal No 9068 of 2019/01 Between Parti Liyani and the Public Prosecutor stated that Parti was acquitted from her sentence because it was not proven. Parti was assisted by a pro-bono lawyer and an NGO called HOME, not by the State of Indonesia. The author analyzes thoroughly using normative legal research methods. Based on the research results, the legal protection provided by the State of Indonesia for Parti is to establish communication to supervise the development of the case. Furthermore, the Indonesian State couldn’t carry out its responsibilities in accordance with Law Number 18 of 2017 concerning PMI Protection, because Parti is not a PMI procedural.